Kesalahan Berbahasa Pada Buletin Cendekia Edisi 1 Tahun 2023 - Syafrida Reza Aulia; Alifia Nur Aini; Muhamad Zakki Imama; Alvionina Maya Amalia; Widya Purwaningsih; Prihatin Sulistyawati (Academica: Journal of Multidisciplinary Studies, 2023)
Indonesian is the national language which must be used in communicating both orally and in writing. However, there are still many errors in the use of language, one of which is the printed media in the bulletin. The purpose of this study is to examine linguistic phenomena in the 1st Edition of the 2023 Scholars Bulletin, and to serve as a correction for writers and readers for other writings. Data was collected using the take note method, by reading the bulletin carefully and noting any errors found. This study uses a qualitative descriptive approach to identify and analyze language errors contained in the bulletin. The results found include errors in: 1) hyphens, 2) italics, 3) punctuation, and 4) use of upper and lower case letters. Based on the results of this study, it is hoped that the public will pay more attention to the use of Ejaan Yang Disesuaikan (EYD) rules.